Dampak Globalisasi terhadap Hukum Tata Negara di Indonesia - Mardiyati, Siti (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
Various aspects of human life have been affected by globalization, including Indonesian constitutional law. This phenomenon has led to increased interactions between countries, technological developments, and the entry of various international legal norms and principles that affect the national legal system. This study aims to analyze the impact of globalization on constitutional law in Indonesia, particularly in the aspects of state sovereignty, democracy, human rights, and government systems. Using normative research methods, this study shows that globalization has positive impacts, such as increased transparency, accountability, and harmonization of national laws with international standards. However, globalization also brings challenges, including the potential weakening of state sovereignty due to the influence of international organizations and global interests. Therefore, an appropriate strategy is needed in responding to globalization so that constitutional law remains adaptive without losing its national characteristics.